PENGEMBANGAN ALAT PENGUKUR POWER TENDANGAN BELADIRI PENCAK SILAT MENGGUNAKAN SENSOR LOADCELL - Kurniawan, Muhammad Farhan; Setiawan, M. Arief; Wijaya, Habibi Hadi (JURNAL ILMU KEOLAHRAGAAN, 2025)
A Loadcell-Based Pencak Silat Kick Strength Measurement Tool This research aims to develop a kick strength measurement tool in the sport of pencak silat, addressing the subjective nature of measurements in the field. The primary technology used is a loadcell sensor to achieve accuracy and standardization. The development model applied is ADDIE (Analysis, Design, Development, Implementation, Evaluation), with a Research and Development (R&D) approach. This tool is equipped with a data recording feature and was tested on five pencak silat athletes from PSHT Bekasi. The test involved three types of kicks: T, crescent, and straight. Through data reading analysis and accuracy tests, the results showed that this tool functions well and accurately, with a very low average error value of 1.58%. This figure proves a high level of precision, making this tool suitable for use in the training process. In conclusion, this measuring tool can be an effective solution to support coaches and athletes in conducting kick evaluations objectively, measurably, and efficiently. In addition, this tool has great potential for further development with additional features in the future.